Планета Земля: справочное издание / Г. М. Абакумова [и др.] - Абакумова Г. М. (Детская энциклопедия РОСМЭН, 2013)
Экземпляры: СФ-1 (20140730) / Инвентарный номер: 41873z1 / Цена: 86.00 / Авт.знак: П 37 / ГРНТИ: 37 / ББК: 26.0